Safety and immunogenicity of inactivated COVID-19 vaccine in patients with metabolic syndrome: A cross-sectional observational study - Guo, Qiao; Yang, Lei; Peng, Ran; Gao, Tao; Chu, Xinglin; Jiang, Depeng; Ke, Dazhi; Ren, Hong (Frontiers in Public Health, 2022)
Background and aims The prevalence of metabolic syndrome (MS), wich mainly including hypertension, hyperglycemia, hyperlipidemia, remains high, and the safety and antibody response of inactivated coronavirus disease 2019 (COVID-19) vaccination in patients with metabolic syndrome (MS) is still inconsistency, therefore it is necessary to explore the safety and antibody responses of inactivated COVID-19 vaccination in MS patients in clinical practice. Methods 157 adults patients who were suffering from MS and 117 health controls (HC) at an interval of at least 21 days after full-course (2nd dose) vaccination were enrolled. The safety of inactivated COVID-19 vaccination was evaluated through collected adverse events (AEs) by questionnaire. The immunogenicity of included participant to inactivated COVID-19 vaccination was represented by serum seropositivity rate of anti-receptor binding domain (RBD) IgG, SARS-CoV-2 neutralizing antibodies (CoV-2 Nab) and titers of anti-RBD IgG, CoV-2 Nab. The B cells, mainly including RBD-specific B cells, RBD-specific memory B cell (MBC), RBD+ resting MBC cells, RBD+ activated MBC cells, RBD+ atypical MBC cells (atyMBCs), and RBD+ intermediate MBC cells, were also analyzed. Results In terms of safety, all AEs in MS patients were mild and self-limiting, and the incidence was comparable to that of HC participants, with overall AEs within seven days reported in 9.6% (15/157) of 3H and 11.1% (13/117) of HC. Both groups experienced no serious adverse events. As for immunogenicity of MS patients to inactivated COVID-19 vaccination, compared with health controls, the seroprevalence of anti-RBD IgG and CoV-2 Nab was significantly decreased in MS patients (p = 0.000, p = 0.003, respectively), while the titers of anti-RBD IgG (AU/ml) and CoV-2 Nab (μg/ml) were also significant lower in MS patients (p = 0.014, p = 0.002, respectively). As for frequencies of B cells, MS patients had lower frequencies of RBD-specific B cells, RBD+ resting MBCs, and RBD+ intermediate MBCs (p = 0.003, p = 0.000, p = 0.000, respectively), but had a higher frequencies of RBD+ atypical MBCs (p = 0.000) than HC. In comorbidity number subgroups analysis of MS, except frequencies of RBD+ resting MBC cells, RBD+ activated MBC cells and RBD+ intermediate MBC cells had significant difference among three groups (p = 0.035, p = 0.042, p = 0.046, respectively), antibody response had no significant difference among 1H, 2H, and 3H groups (p > 0.05). And took 70 years old as a boundary, also no statistically significant differences (p > 0.05) were found in age subgroups. Lastly, comprehensive analysis in MS patients indicated that interval time after 2nd dose vaccine was the statistical significant factor which impacting antibody response in MS individuals. Conclusions Inactivated COVID-19 vaccines were well-tolerated, but induced a poorer antibody response against SARS-CoV-2 in MS patients comparing to HC participants. Patients with MS should therefore be more proactive in receiving inactivated COVID-19 vaccine, and a booster vaccination may be considered necessary. Clinical trial registration https://clinicaltrials.gov/, identifier: NCT05043246.